Spectroscopic Investigation for Photo stability of Hydrochlorothiazide Complexes with Î²-Cyclodextrin and HPMC. - Dhekale, Pallavi Shrirang (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Hydrochlorothiazide (HCT) is a poorly water-soluble drug. The aim of this study was to determine whether inclusion complexes between Î²-cyclodextrin and HCT are formed and also studied effect of auxiliary substance (HPMC) on HCT, photo-stability of HCT and to characterize these. Equimolar HCT/ Î²CD solid systems in the presence or absence of 0.2% (w/v) of HPMC were prepared by kneading method. The systems were characterized by phase solubility, Dissolution study, FTIR, DSC and the photo-stability test followed by u.v. spectroscopy. Â The results suggest that true binary and ternary inclusion complex. The test results have proved that the complexed HCT with hydroxypropyl Î²- cyclodextrin enhance the photo degradation rate and resolute the optimal molar ratio HCT to hydroxypropyl Î²- cyclodextrin as 1:1.